Mission Tracks in the Bush: Theological Reflections on Two Aboriginal Missions in Nineteenth-Century Australia - Cruz, Gemma Tulud (Interreligious studies and intercultural theology, 2019)
Christian missionaries played an important role in the Australian nation building that started in the nineteenth century. This essay explores the multifaceted and complex cultural encounters in the context of two aboriginal missions in Australia in the nineteenth century. More specifically, the essay explores the New Norcia mission in Western Australia in 1846-1900 and the Lutheran mission in South Australia in 1838-1853. The essay begins with an overview of the history of the two missions followed by a discussion of the key faces of the cultural encounters that occurred in the course of the missions. This is followed by theological reflections on the encounters in dialogue with contemporary theology, particularly the works of Robert Schreiter.